Development of IT - Based Mathematics Learning Media Using Articulate Storyline - Fadhila, Nurul; Rahmi, Rahmi; Hamdunah, Hamdunah (Al-Khawarizmi, 2022)
This research is motivated by the lack of motivation and participation of students in participating in learning mathematics. The purpose of this study was to produce a valid and practical IT-based mathematics learning media on Data Presentation material at SMP N 1 Padang Ganting. The type of research used is development research using the ADDIE development model. The research instrument used was a validation questionnaire, a practicality questionnaire that was useful to see the practicality of learning media by teachers and students. The results of the validity of IT-based learning media using Articuate Storylineby 98% with a very valid category. The final value of practicality with the teacher obtained a final score of 100% in the very practical category. The final value of practicality with students was obtained 96.7% in the very practical category. Based on the results of the study, it can be concluded that IT-based learning media using Articuate Storyline is declared valid and practical to use in learning data presentation materials at SMP N 1 Padang Ganting.